The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jmb.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Functionally Important Conformational Changes in Proteins: Activation of the Yeast α-factor Receptor Ste2p

Abstract: We have developed a procedure in which disulfide crosslinks are used to identify regions of proteins that undergo functionally important intramolecular motion. The approach was applied to the identification of disulfide bonds that stabilize the active state of the yeast α-mating pheromone receptor Ste2p, a member of the superfamily of G Protein Coupled Receptors. Cysteine residues were introduced at random positions in targeted regions of a starting allele of Ste2p that completely lacks cysteines. Libraries of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Full-length alleles of STE2 consisted of fusions to three copies of the influenza HA epitope tag. C-terminally truncated alleles of STE2 were fused to a triple c-myc epitope tag, as described previously 75 . For immunoblotting of cell lysates, strains were cultured in SD-ura to an OD 600 of 1.…”
Section: Methodsmentioning
confidence: 99%
“…Full-length alleles of STE2 consisted of fusions to three copies of the influenza HA epitope tag. C-terminally truncated alleles of STE2 were fused to a triple c-myc epitope tag, as described previously 75 . For immunoblotting of cell lysates, strains were cultured in SD-ura to an OD 600 of 1.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pMD1887, containing full duplication of the 16-residues IC3 loop, but no inserted T4L, was created by oligonucleotide-directed mutagenesis (oligonucleotide ON 1424) of plasmid pMD1886, recovered from the library screen, that contained 16 residues of IC3, followed by T4L, followed by 15 residues of IC3. Yeast strain A2953 (Taslimi et al, 2012) was used for screening of insertional libararies. Strain A575 (Sommers et al, 2000) was used for retransformation with identified STE2 alleles for further characterization.…”
Section: Yeast Plasmids and Strainsmentioning
confidence: 99%
“…In another study, the K225C mutation ablated functionality of the native Ste2p receptor [15], so it is noteworthy that a substitution to a similarly nucleophilic residue (K225T) did not ablate receptor functionality here. K225T is on the border of the third intracellular loop and the fifth transmembrane region, the relative motion of which is required for receptor activation [11]. If the K225T mutation is destabilizing, a possible explanation for the beneficial nature of the K225T mutation in the Mut2 receptor is that the mutation destabilizes the receptor enough to accept a nonnative ligand, but the M218T mutation, which was noted as a rescuing mutation earlier in this discussion, rescues this destabilization.…”
Section: Critical and Beneficial Mutations For Peptide Detectionmentioning
confidence: 82%
“…M218T is located in the fifth transmembrane region, the relative motion of which is required for receptor activation [11]. In the context of the native Ste2p, M218T on its own is a neutral mutation, and residue 218 is believed to interact with residues on the third transmembrane region.…”
Section: Critical and Beneficial Mutations For Peptide Detectionmentioning
confidence: 99%